The relationship of academic aptitude and study habits to academic success : a study of first year students' experience of academic life with specific reference to the University of Fort Hare - Penny, Alan Joseph (Rhodes University, Faculty of Education, Department of Education, 1980)
Any enquiry follows some incident which has prompted the question that leads to the enquiry. This study was prompted by a review of the 1974 first year examination results at the University of Fort Hare. The average percentage pass rate for that year was 59.3%. The cynic may remark that this is no different to the first year pass rate at white South African universities (cf. Erens and Louw, 1978), but when it is realised that students entering Fort Hare, or any other black university for that matter, are a highly select group, these figures have more Impact. The consequences of failure in terms of the wastage of human potential are immense (cf. Auerbach, 1977) but are more critical when this occurs, as It does, "... in a society which is competitive rather than co-operative, where people are for ever being classified according to what they have rather than that they can contribute and where competition plus classification inevitably breeds fears." Bligh (1978). A review of the first year examination results for the five years from 1971 revealed an average pass rate of 55.5% and for 1976, 1977 and 1978 a marked decline to 39.32%. For the earlier period, Downing (1977) found that 19.69% of students completed their degree courses In the minimum number of years. For the latter period (1976 to 1978) this has dropped to 16.3%, which, with the figure for the earlier period, suggests that whilst the failure rate may be highest at the end of the first year, in subsequent years it is also high. In this respect Fort Hare differs from white universities where about 75% of students complete their degrees in minimum time (cf. Erens and Louw, 1978)
Keywords: Academic achievement; Student adjustment -- South Africa; College students, Black -- South Africa